The Common Marmoset—Biomedical Research Animal Model Applications and Common Spontaneous Diseases. (July 2022) - Han, Hyo-Jeong; Powers, Sarah J.; Gabrielson, Kathleen L.
Marmosets are becoming more utilized in biomedical research due to multiple advantages including (1) a nonhuman primate of a smaller size with less cost for housing, (2) physiologic similarities to humans, (3) translatable hepatic metabolism, (4) higher numbers of litters per year, (5) genome is sequenced, molecular reagents are available, (6) immunologically similar to humans, (7) transgenic marmosets with germline transmission have been produced, and (8) are naturally occurring hematopoietic chimeras. With more use of marmosets, disease surveillance over a wide range of ages of marmosets has been performed. This has led to a better understanding of the disease management of spontaneous diseases that can occur in colonies. Knowledge of clinical signs and histologic lesions can assist in maximizing the colony's health, allowing for improved outcomes in translational studies within biomedical research. Here, we describe some basic husbandry, biology, common spontaneous diseases, and animal model applications for the common marmoset in biomedical research.